Investigation of Peripheral Effects of Citrus Limon Essential Oil on Somatic Pain in Male Wistar Rats: Role of Histaminergic System - Ali Mojtahedin (Fasa University of Medical Sciences, 2016)
Background & Objective: One of the plants used in traditional medicine is lemon which has analgesic effect. However, little research has been performed on the analgesic effect of lemon and mechanisms of action with an emphasis on neurotransmitters systems. Therefore, the present study set to investigate the peripheral effects of lemon essential oil on somatic pain using formalin test with an emphasis on histaminergic system in male Wistar rats. Materiala & Methods: Sixty male rats weighing approximately 200-250g and aged 14-16 wk were divided into 10 groups: sham (Salin + Formalin 1% intraplantar), three treatment groups with lemon essential oil (EO) (12.5, 25 and 50 mg/kg), three treatment groups with Chlorpheniramine (5, 10 and 20 mg/kg), 1 treatment group with Histamine (10 mg/kg), 1 pretreatment group with Chlorpheniramine (20 mg/kg) + EO (50mg/kg), and 1 pretreatment group with Histamine (10 mg/kg) + EO (50 mg/kg). Formalin test was used to assess somatic pain. Data analysis was performed using one-way ANOVA. Results:  Intraperitoneal injection of lemon essential oil reduced the pain response induced by formalin in both phases (P<0.05). Pretreatment with chlorpheniramine and lemon essential oil enhanced the analgesic response in both phases (P<0.05). Conclusion: Lemon essential oil had analgesic effects, probably caused by the histaminergic system.